Objektivizace pooperačních výsledků nitroočních čoček - Nekolová, J; Langrová, H; Rozsíval, P; Jirásková, N (Ceska a slovenska oftalmologie, 2016)
PURPOSE: To prospectively compare postoperative results of two premium intraocular lenses EnVISTA (Bausch and Lomb) and AcrySof IQ (Alcon), focussing on glistenings and posterior capsule opacification. The evaluation of glistenings was done using Image J software and posterior capsule opacifications were quantified with OSCA system. METHODS: Twenty patients (7 men and 13 women) with bilateral cataract were included. EnVista intraocular lens (IOL) was implanted in one eye and AcrySof IQ IOL in the second eye of each patient. Objective evaluation methods were used for assessment. Glistenings was quantified with ImageJ software and PCO using the Open-Access Systematic Capsule Assessment (OSCA) system (Devised by Aslam TM, Edinburgh, United Kingdom). Complete ophthtalmological evaluation including evaluation after pupil dilatation was done and digital images of intraocular lenses were obtained. The results of 2-, 4-, 6- and 12-month follow-up were compared. RESULTS: Twenty patients were analyzed 2 months, 16 patients 4 months, 14 patients 6 months and 13 patients 12 months after cataract surgery. There was only minimal difference in best corrected visual acuity between EnVista and AcrySof group. The glistenings in the EnVista IOLs was objectively lower than in the AcrySof IOLs during whole follow-up period. In contrast to PCO, in eyes with AcrySof IOL was lower PCO score. CONCLUSION: Development of new materials and techniques of cataract surgery is the topic of ophthtalmologists worldwide. Reduction of glistenings and PCO is one of the main aims, objective measurements is important part of assessment of postoperative results after cataract surgery. KEY WORDS: glistenings, posterior capsule opacification, EnVista, AcrySof IQ, Image J software, OSCA system.
Keywords: výsledek terapie; Postoperative Period; Male; zraková ostrost; Prosthesis Design; Acrylic Resins; implantace nitrooční čočky; protézy - design; Lenses, Intraocular; následné studie; akrylové pryskyřice; Capsule Opacification; Pseudophakia; pseudofakie; Aged; Prospective Studies; mužské pohlaví; senioři; Visual Acuity; zkalení zadního pouzdra čočky; Follow-Up Studies; pooperační období; Cataract Extraction; Treatment Outcome; nitrooční čočky; lidé; ženské pohlaví; Lens Implantation, Intraocular; Humans; extrakce katarakty; Phacoemulsification; Female; fakoemulzifikace; prospektivní studie